Xavier Bougarel, Hannes Grandits, Marija Vulesica, ur., Local Dimensions of the Second World War in Southeastern Europe (London; New York: Routledge, Taylor & Francis Group, 2019), xi + 281 str. (Časopis za suvremenu povijest, 2020)
Prikaz knjige